Can the hoof be shod without limiting the heel movement? A comparative study between barefoot, shoeing with conventional shoes and a split-toe shoe. (April 2019) - Brunsting, J.; Dumoulin, M.; Oosterlinck, M.; Haspeslagh, M.; Lefère, L.; Pille, F.
Highlights: A potentiometer was used to quantify heel movement in barefoot and shod horses at the walk, trot and canter on a treadmill. After application of a conventional shoe, there was a 36.3% decrease in heel expansion compared with barefoot. An innovative horseshoe with a split toe was tested for its ability to overcome the issue of limiting the hoof mechanism. The application of a split-toe shoe was associated with significantly more heel expansion than the conventional shoe. Heel expansion with the split-toe shoe did not differ significantly from barefoot. Abstract: Conventional shoeing restricts heel movement, which may have a negative effect on the orthopaedic health of the horse. A randomised crossover experimental study using noninvasive techniques was performed to compare the mediolateral heel movement in barefoot horses, horses shod with a conventional toe clipped shoe and with a new type of shoe with a split toe. In eight horses, 16 forelimbs were tested barefoot, shod with a conventional shoe and with the split-toe (ST) shoe, in random order. A displacement sensor was secured on the heels and measurements were collected continuously at a frequency of 679 Hz while horses were exercised on a treadmill at the walk (1.8 m/s), trot (3.5 m/s) and canter (8 m/s). Differences in heel movement between the conditions were analysed using a generalised estimating equations approach. The conventional shoe was associated with significantly less heel expansion compared with the ST shoe and barefoot situation in all gaits ( P ≤ 0.001). Heel expansion with the ST shoe was not significantly different from the barefoot condition. For all gaits, shoeing was associated with a significant reduction in heel contraction compared with the barefoot situation ( P ≤ 0.038), except for the heel contraction at the canter using a conventional shoe. In conclusion, the heel expansion with the ST shoe did not differ significantly from when the horse was barefoot, in contrast with the significant restriction of the heel movement when a conventional shoe was used.